The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/jmv.21299
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 6 integrates within telomeric regions as evidenced by five different chromosomal Sites

Abstract: Fluorescent in situ hybridization (FISH) was used to investigate the chromosomal integration sites of human herpesvirus 6 (HHV-6) in phytohemagglutinin-stimulated leukocytes and B lymphocytes from Epstein-Barr virus transformed lymphoblastoid cell lines (LCLs). Five different chromosomal integration sites were found in nine individuals. Only one site was identified in each individual, each site was in the vicinity of the telomeric region and was on either the p or q arm of only one of the two chromosome homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
79
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 37 publications
2
79
0
3
Order By: Relevance
“…Previous research has identified occasional patients with high copy numbers of HHV-6 DNA and FISH results suggesting chromosome integrated HHV-6 (19)(20)(21)(22)(23)(24)(25). Often the same findings occur in both parents and children, suggesting vertical transmission in the germline.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous research has identified occasional patients with high copy numbers of HHV-6 DNA and FISH results suggesting chromosome integrated HHV-6 (19)(20)(21)(22)(23)(24)(25). Often the same findings occur in both parents and children, suggesting vertical transmission in the germline.…”
Section: Resultsmentioning
confidence: 89%
“…However, some studies using FISH analysis have suggested that both HHV-6A and B can integrate into human chromosomes (19)(20)(21)(22)(23)(24)(25) and may be vertically transmitted in the germ line (26). FISH assay, however, cannot distinguish noncovalent linkage from integration, establish the specific integration site, or determine whether the integrated virus can reactivate and produce infectious virions.…”
mentioning
confidence: 99%
“…HHV-6A/B integration can occur in various chromosomes, with viral genomes consistently detected in telomeric regions that are located at chromosome termini (5,10,(13)(14)(15). Telomeres are composed of double-stranded TTAGGG repeats (8 to 13 kbp long) followed by a 30-to 200-bp single-stranded 3= overhang (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…9,10 HHV-6 is unique among the human herpesviruses in that the whole viral genome is integrated into one of several different human chromosomes at the telomere in 0.2% to 0.8% of the population and passed from parent to child in the germline via Mendelian inheritance. 11,12 The clinical relevance of congenital infection with HHV-6 is undefined but may be similar to CMV and associated with developmental disability.…”
mentioning
confidence: 99%